Malnutrition Is an Independent Risk Factor for Low Health-Related Quality of Life Among Centenarians - Yang, Shanshan; Wang, Shengshu; Liu, Wei; Han, Ke; Jia, Wangping; Liu, Miao; He, Yao (Frontiers in Medicine, 2021)
Background: To explore the association and understand gender disparities between nutritional status and quality of life among centenarians. Methods: It was a full-sample survey of centenarians conducted in Hainan that included a total of 1,002 eligible centenarians whose age had been verified. The Mini Nutritional Assessment – Short Form (MNA-SF) questionnaire and the EuroQol five dimensions visual analog scale (EQ-5D-VAS) were used to measure participants’ nutritional status and quality of life, respectively. Findings: In the 1002 centenarians (822 women and 180 men), 797 (79·5%) reported multimorbidity. The adjusted standardized β estimate for the association between the MNA-SF and EQ-5D scores was 0·508 in the complete sample. With reference to the normal nutrition group, the standardized β estimate of the association between EQ-5D score and nutritional status were −0·179 and −0·583 for the at risk of malnutrition and malnutrition groups, respectively (both P <0·001). Nutritional status significantly affected the five dimensions of quality of life, particularly mobility and self-care. Compared with the normal nutrition group, the malnutrition group had greater odds of low mobility (Odds ratio (OR)=23·15; 95% CI: 9·81–54·64) and low self-care (OR=24·58; 95% CI: 12·62–47·89). Among males, nutritional status was significantly associated with the usual activities and anxiety/depression dimensions after adjustment. Female participants had results similar to the general population. Interpretation: Malnutrition and being at risk of malnutrition is prevalent among centenarians. Maintaining normal nutritional status is an important protective factor and should receive more attention to improve centenarians’ quality of life.